Near infrared spectroscopy (NIRS) as tool for classification into official commercial categories and shelf-life storage times of pre-sliced modified atmosphere packaged Iberian dry-cured loin. (15th September 2021) - Tejerina, David; Contador, Rebeca; Ortiz, Alberto
Highlights: Authentication of pre-sliced MAP Iberian dry-cured loin could be possible by NIRS. Storage time of pre-sliced MAP Iberian dry-cured loin could be assigned using NIRS. Best predictive ability was obtained for Black category by PLS-DA. SIMCA provided low specificity between Iberian quality categories and storage times. Abstract: The potential of Near Infrared Spectroscopy combining different spectral treatments and classification models was assessed for the classification of individual pre-sliced Iberian dry-cured loin packaged under modified atmosphere packaging (MAP) into three official commercial categories (which involve the breed purity and production system) according to the current Iberian Quality Standard ( Black, Red and White ) and for the assignment to the shelf-life time (0, 4, 8 and 12 months). External validation results provided acceptable results, with up to 100% of samples correctly assigned to Black and White official commercial category and into all storage times. Actually the 100% assignments were obtained using more than one approach (SIMCA and LDA for commercial categories and PLS-DA, SIMCA and LDA for storage times). These results might contribute to support the on-line control of authenticity of official commercial category and to facilitate the monitoring of the quality of pre-package dry-cured products throughout the shelf-life prediction.